Features of Tax Regulation of Banks’ Activities and Impact on Financial Activities - Sayfidinovich, Komolov Odiljon (PT. Riset Press International, 2025)
This article is devoted to the foreign experience of taxation of commercial banks, and within the framework of the study, the research of foreign and domestic scientists was studied. Taxes paid by banks are always of particular importance in the economic activities of commercial banks. Also, a comparative analysis of the tax policies implemented by foreign countries and the lessons learned from them is presented, and a conclusion is drawn at the end.